"Our mothers do not tell us": a qualitative study of adolescent girls' perspectives on sexual and reproductive health in rural Nepal. Issue 2 (1st January 2022) - Tiwari, Aparna; Wu, Wan-Ju; Citrin, David; Bhatta, Aasha; Bogati, Bhawana; Halliday, Scott; Goldberg, Alisa; Khadka, Sonu; Khatri, Rekha; Kshetri, Yashoda; Rayamazi, Hari Jung; Sapkota, Sabitri; et al.
Abstract: Adolescent girls in low- and middle-income countries continue to face poor sexual and reproductive health (SRH). In Nepal, early marriage and motherhood, gender-based violence, and unmet need for contraception remain pervasive. Adolescent girls in rural areas bear a disproportionate burden of poor reproductive health outcomes, but there are limited context-specific data. This is a qualitative study to identify factors that impact adolescent girls' utilisation of and access to SRH services in a rural district of Nepal. We conducted 21 individual interviews with adolescent girls aged 15–19 years, and three focus group discussions with community health workers. We used an inductive analytic approach to identify emergent and recurrent themes and present the themes using the social ecological model. Individual-level factors that contribute to low uptake of services among adolescent girls include lack of knowledge, self-perceived lack of need, low decision-making autonomy, and shyness. Interpersonal factors that impact access include unsupportive family norms, absence of open communication, and need for permission from family members to access care. At the community level, disparate gender norms, son preference, and judgment by community members affect adolescent SRH. Inadequate sex education, far travel distance to facilities, lack of female healthcare providers and teachers, and inability to access abortion services were identified as organisational and systems barriers. Stigma was a factor cross-cutting several levels. Our findings suggest the need for multi-level strategies to address these factors to improve adolescent girls' SRH.